2011
DOI: 10.1002/cncr.26180
|View full text |Cite
|
Sign up to set email alerts
|

21‐Gene recurrence scores

Abstract: BACKGROUND: African American (AA) women experience higher breast cancer mortality than white (W) women. These differences persist even among estrogen receptor (ER)-positive breast cancers. The 21-gene recurrence score (RS) predicts recurrence in patients with ER-positive/lymph node-negative breast cancer according to RS score-low risk (RS, 0-18), intermediate risk (RS,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), and high risk (RS, >31). The high-risk group is most likely to benefit from chemotherapy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 27 publications
(56 reference statements)
3
28
1
Order By: Relevance
“…This differs significantly from preliminary ODX validation studies, where 27 % of women with early-stage breast cancer were classified as high risk [6]. Notably, subsequent observational studies have found the proportion of high-risk scores to be similar to what we observed [9]. In a qualitative study, providers discussed being less likely to order ODX testing for more aggressive tumors, because they felt that they already had the necessary information to offer adjuvant chemotherapy [15].…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…This differs significantly from preliminary ODX validation studies, where 27 % of women with early-stage breast cancer were classified as high risk [6]. Notably, subsequent observational studies have found the proportion of high-risk scores to be similar to what we observed [9]. In a qualitative study, providers discussed being less likely to order ODX testing for more aggressive tumors, because they felt that they already had the necessary information to offer adjuvant chemotherapy [15].…”
Section: Discussioncontrasting
confidence: 87%
“…In the intermediate-risk group, Black women had slightly higher ODX risk scores than non-Black women. However, the magnitude of this difference was small, and likely not clinically meaningful, corroborating a previous study that reported no significant racial differences in mean ODX risk scores [9]. Unlike that study, we did not observe significant racial differences in the distribution of women into ODX risk groups [9].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Previous studies, mainly conducted in a US health care setting, report contradictory results on the association between race, median income or educational status and GEP use. Some observed disparities [13,15,18], whereas others found no differences in GEP uptake [11,12]. In a US health care setting, disparities in GEP uptake between different socioeconomic classes may well be explained by financial inequalities.…”
Section: Discussionmentioning
confidence: 99%